Suitability analysis of spiny lobster mariculture zones in Sabang waters, Indonesia - Ismail Ismail; Muhammadar Muhammadar; Firdus Firdus (Depik, 2023)
The lobster aquaculture industry has a high dependence on natural catch. Hence, lobster farming has become necessary. The waters in Sabang have the potential for developing lobster mariculture, but data is not yet available on the conditions of the aquatic environment that are suitable for lobster farming. This research aims to determine which locations are suitable for lobster mariculture activities in the waters of Sabang. The research parameters are divided into geographics, physicochemical, and supporting parameters. The geographical parameters group was collected through in-situ observations, and physicochemical parameters were measured in-situ and laboratory tests, supporting parameters through observations. Initial data analysis used the SAW (Simple Additive Weighting), AHP (Analysis Hierarchy Process) methods, and spatial analysis to determine the suitability of lobster cultivation zones with the Geographic Information System (GIS). From the observations of geographical parameters, the three locations of the observation station were in the very suitable category. The results of measuring physicochemical parameters group in three research locations were very suitable. Based on observations of other supporting parameters, Lhok Krueng Raya is very suitable for the cultivation zone, while Teupin Sirui and Lhok Weing are suitable. The findings of this research indicate that location protection, accessibility, DO, and COD are limiting parameters for selecting a suitable location for lobster mariculture in Sabang waters.Keywords:Suitability analysisLobster farmingSabangGIS